Factors Associated with the Time of Admission among Notified Dengue Fever Cases in Region VIII Philippines from 2008 to 2014. - Jason Echavez Abello; Julita Gil Cuesta; Boyd Roderick Cerro; Debarati Guha-Sapir (Public Library of Science (PLoS), 2016)
In cases of Dengue fever, late hospital admission can lead to treatment delay and even death. In order to improve early disease notification and management, it is essential to investigate the factors affecting the time of admission of Dengue cases. This study determined the factors associated with the time of admission among notified Dengue cases. The study covered the period between 2008 and 2014 in Region VIII, Philippines. The factors assessed were age, sex, hospital sector, hospital level, disease severity based on the 1997 WHO Dengue classification, and period of admission (distinguishing between the 2010 Dengue epidemic and non-epidemic time). We analysed secondary data from the surveillance of notified Dengue cases. We calculated the association through chi-square test, ordinal logistic regression and linear regression at p value < 0.05. The study included 16,357 admitted Dengue cases. The reported cases included a majority of children (70.09%), mild cases of the disease (64.00%), patients from the public sector (69.82%), and non-tertiary hospitals (62.76%). Only 1.40% of cases had a laboratory confirmation. The epidemic period in 2010 comprised 48.68% of all the admitted cases during this period. Late admission was more likely among adults than children (p<0.05). The severe type of the disease was more likely to be admitted late than the mild type (p<0.05). Late admission was also more likely in public hospitals than in private hospitals (p<0.05); and within tertiary level hospitals than non-tertiary hospitals (p<0.05). Late admission was more likely during the non-epidemic period than the 2010 epidemic period (p<0.05). A case fatality rate of 1 or greater was significantly associated with children, severe diseases, tertiary hospitals and public hospitals when admitted late (p<0.05). Data suggests that early admission among child cases was common in Region VIII. This behavior is encouraging, and should be continued. However, further study is needed on the late admission among tertiary, public hospitals and non-epidemic period with reference to the quality of care, patient volume, out of pocket expense, and accessibility We recommend the consistent use of the 2009 WHO Dengue guidelines in order to standardize the admission criteria and time across hospitals.